A graphene aerogel self-repairing asphalt concrete and its application
By introducing the graphene gas gel fixed asphalt self -repair agent in the asphalt concrete, the combination of graphene gas gel matrix and asphalt regeneration agent is used to achieve the efficient self -repair of asphalt concrete, solving the low efficiency and low repair efficiency in the existing technology and the The problem of damage to the substrate has significantly improved the service life and self -repair effect of asphalt pavement.
Patent Information
- Application Number
- CN202211587821.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-11
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2042-12-11
AI Technical Summary
The existing asphalt concrete self-repair technology has low repair efficiency and limited effect, and the introduction process of microcapsules has an adverse impact on the mechanical properties of the matrix, making it difficult to promote and apply.
A graphene airgel-shaped asphalt self-healing agent is used to form a graphene airgel self-healing asphalt concrete by adding a graphene airgel matrix and an asphalt regenerator to the asphalt mixture matrix. In the field of electrothermal self-healing, this technology realizes the self-healing of asphalt concrete through constant electric power stimulation.
It has significantly improved the mechanical performance, durability and anti -fatigue performance of asphalt concrete, extended the service life of the actual application of asphalt pavement, and improved the timeliness of self -repair.
Smart Images

Figure CN116081979B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of road repair, and in particular to a graphene aerogel self-repairing asphalt concrete and its application. Background Art
[0002] Asphalt pavement is prone to rutting, cracking and other damages under the combined effects of vehicle loads and the environment, which seriously affect its performance and service life. Therefore, if the active regulation and self-repair of the asphalt pavement matrix can be achieved at the early stage of microcracks and microdamage, macroscopic damages such as fatigue cracking and aging caused by the further development of cracks can be effectively avoided, thereby improving the performance and service life of the asphalt pavement and promoting the sustainable development of the transportation industry.
[0003] Most of the existing asphalt concrete self-repair technologies focus on microcapsule self-repair technology, but the repair efficiency is low and the effect is limited, and it can only achieve one-time repair. In addition, the wall materials of microcapsules are mostly polymer materials with weak mechanical properties. The introduction process of microcapsules will have an adverse effect on the mechanical properties of the asphalt concrete matrix, which increases the difficulty and limitations of its promotion and application process. Summary of the invention
[0004] The purpose of the present invention is to provide a graphene aerogel self-healing asphalt concrete and its application in order to overcome the defects of the above-mentioned prior art, such as the single healing form of the self-healing asphalt concrete matrix material and the adverse effects on the matrix strength and service performance.
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] One of the technical solutions of the present invention is to provide a graphene aerogel self-repairing asphalt concrete, which is composed of an asphalt mixture matrix and a graphene aerogel-shaped asphalt self-repairing agent distributed in the asphalt mixture matrix.
[0007] Furthermore, the addition amount of the graphene aerogel shaped asphalt self-repairing agent is 0.2-3.0% of the total mass of the graphene aerogel self-repairing asphalt concrete.
[0008] Furthermore, the graphene aerogel-shaped asphalt self-healing agent consists of a graphene aerogel matrix and an asphalt regeneration agent filled in the pores of the graphene aerogel matrix.
[0009] Furthermore, the graphene aerogel matrix is a three-dimensional porous aerogel composed of carbon nanomaterials.
[0010] Furthermore, the carbon nanomaterial is selected from one or more of graphene and carbon nanotubes.
[0011] Furthermore, the porosity of the graphene aerogel matrix is 30%-99%.
[0012] Furthermore, the graphene aerogel matrix is selected from one or more of a fiber-type graphene aerogel matrix, a particle-type graphene aerogel matrix, and a fiber-type graphene / carbon nanotube composite aerogel matrix.
[0013] Furthermore, the fiber-type graphene aerogel matrix has a length of 6-20 mm and a diameter of 10-500 μm; the particle size of the particle-type graphene aerogel matrix is 10-20 mm; the fiber-type graphene / carbon nanotube composite aerogel matrix has a length of 6-20 mm and a diameter of 10-500 μm.
[0014] The second technical solution of the present invention is to provide an application of the graphene aerogel self-healing asphalt concrete as described in the first technical solution, wherein the graphene aerogel self-healing asphalt concrete is applied to the field of electrothermal self-healing. Electrothermal self-healing is the healing of crack damage in asphalt concrete under the maintenance of electric heat as an excitation condition.
[0015] Furthermore, in the application of electrothermal self-repairing, the graphene aerogel self-repairing asphalt concrete is stimulated by a constant electric power of 10-200W.
[0016] Compared with the prior art, the present invention has the following beneficial effects:
[0017] (1) The graphene aerogel matrix has excellent mechanical strength and good stability, which can significantly improve the mechanical properties and durability of asphalt concrete, thereby showing excellent anti-fatigue performance and better serving pavement engineering.
[0018] (2) Graphene aerogel-shaped asphalt self-healing agent can effectively improve the self-healing performance of asphalt concrete. During the microcrack propagation process of damaged asphalt concrete, the stress at the crack tip drives the graphene aerogel matrix to release the asphalt regeneration agent, which interacts with the aged asphalt to complete its in-situ regeneration, realizes the active healing of cracks, significantly improves the mechanical properties and durability of damaged asphalt concrete, and extends the service life of asphalt pavement in actual application.
[0019] (3) The excellent conductive properties of the graphene aerogel matrix enhance the conductivity of graphene aerogel self-healing asphalt concrete, promoting the efficient healing of asphalt concrete crack damage under the maintenance of electric heat as the excitation condition, solving the limitations of low repair efficiency and single form of traditional self-healing asphalt concrete, and improving the maintenance efficiency and self-healing time of asphalt pavement materials in the application process. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1Schematic diagram of the structure of graphene aerogel self-repairing asphalt concrete.
[0021] Figure 2 Schematic diagram of the structure of graphene aerogel-shaped asphalt self-healing agent: (a) granular graphene aerogel-shaped asphalt self-healing agent; (b) fiber-type graphene aerogel-shaped asphalt self-healing agent.
[0022] Figure 3 It is a schematic diagram of the application of an embodiment of the present invention in the field of electrothermal self-repair.
[0023] Description of the numbers in the figure:
[0024] 1-asphalt mixture matrix; 2-graphene aerogel-shaped asphalt self-healing agent; 3-graphene aerogel matrix; 4-asphalt regeneration agent; 5-electrode; 6-crack damage. DETAILED DESCRIPTION
[0025] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0026] In the following examples and comparative examples, unless otherwise specified, raw materials or processing techniques are conventional commercially available raw materials or conventional processing techniques in the art.
[0027] Asphalt self-regeneration agent 4 is commercially available ERA-C asphalt regeneration agent.
[0028] The asphalt mixture used in the asphalt mixture matrix 1 adopts AC-13 grading, the content of 70#A road petroleum asphalt is 4.9%, and the oil-stone ratio is 5.15%; the softening point of 70#A road petroleum asphalt is 47.0°C, and the needle penetration is 74 (0.1mm).
[0029] The preparation methods of the particle-type graphene aerogel matrix, the fiber-type graphene / carbon nanotube composite aerogel matrix, and the fiber-type graphene aerogel matrix prepared by the hydrothermal reduction method refer to A review on elastic graphene aerogels: Design, preparation, and applications, Yuxing Xia, et al. Journal of Polymer Science, Volume 60, Issue 15, Pages 2239-2261.
[0030] Embodiment 1:
[0031] like Figure 1As shown, a graphene aerogel self-repairing asphalt concrete is composed of an asphalt mixture matrix 1 and a graphene aerogel-shaped asphalt self-repairing agent 2 distributed in the asphalt mixture matrix 1. The addition amount of the graphene aerogel-shaped asphalt self-repairing agent 2 is 0.6% of the total mass of the graphene aerogel self-repairing asphalt concrete. During the mixing process of the asphalt mixture matrix 1, the graphene aerogel-shaped asphalt self-repairing agent 2 is added to obtain the graphene aerogel self-repairing asphalt concrete.
[0032] like Figure 2 As shown, the graphene aerogel-shaped asphalt self-repairing agent 2 is composed of a graphene aerogel matrix 3 and an asphalt regeneration agent 4 filled in the pores of the graphene aerogel matrix 3. Figure 2 As shown in (a), the graphene aerogel matrix 3 is a granular graphene aerogel matrix prepared by hydrothermal reduction, with an average particle size of 100 μm and a porosity of 53.6%. The asphalt regeneration agent 4 is loaded into the graphene aerogel matrix 3 by vacuum adsorption, thus obtaining the graphene aerogel-shaped asphalt self-healing agent 2.
[0033] This embodiment 1 also includes an evaluation of the self-repairing effect of the above-mentioned graphene aerogel self-repairing asphalt concrete:
[0034] Asphalt concrete slabs of 400mm×300mm×75mm were made according to the vibration wheel rolling method and cut into curved beams. The American AASHTO T321 standard was used to carry out strain-controlled four-point bending fatigue test and determine the fatigue life of the asphalt concrete.
[0035] The asphalt concrete bending beam that reached the fatigue end condition was placed at 20°C for 48 hours, and then the asphalt concrete bending beam was subjected to the above fatigue test again. The fatigue life recovery rate was used to evaluate the self-healing effect of asphalt concrete, that is, the increased fatigue life after healing / fatigue life.
[0036] The results show that the fatigue life recovery rate of the graphene aerogel self-healing asphalt concrete bending beam reaches 76.9%, indicating that the graphene aerogel self-healing asphalt concrete has a relatively ideal self-healing effect.
[0037] Embodiment 2:
[0038] A graphene aerogel self-repairing asphalt concrete of this embodiment 2 is composed of an asphalt mixture matrix 1 and a graphene aerogel-shaped asphalt self-repairing agent 2 distributed in the asphalt mixture matrix 1. The addition amount of the graphene aerogel-shaped asphalt self-repairing agent 2 is 1.0% of the total mass of the graphene aerogel self-repairing asphalt concrete. During the mixing process of the asphalt mixture matrix 1, the graphene aerogel-shaped asphalt self-repairing agent 2 is added to obtain the graphene aerogel self-repairing asphalt concrete.
[0039] The graphene aerogel-shaped asphalt self-repairing agent 2 is composed of a graphene / carbon nanotube composite aerogel matrix and an asphalt regeneration agent 4 filled in the graphene / carbon nanotube composite aerogel matrix. Figure 2 As shown in (b), the graphene / carbon nanotube composite aerogel matrix is a fiber-type graphene / carbon nanotube composite aerogel matrix prepared by hydrothermal reduction method, with a length of 6 mm, a diameter of 50 μm, and a porosity of 44.6%. By vacuum adsorption method, the asphalt regeneration agent 4 is contained in the graphene aerogel matrix 3, and the graphene aerogel-shaped asphalt self-healing agent 2 is obtained.
[0040] This embodiment 2 also includes the application of the above-mentioned graphene aerogel self-repairing asphalt concrete in the field of electrothermal self-repairing and the evaluation of the self-repairing effect:
[0041] Asphalt concrete slabs of 400mm×300mm×75mm were made according to the vibration wheel rolling method and cut into curved beams. The American AASHTO T321 standard was used to carry out strain-controlled four-point bending fatigue test and determine the fatigue life of the asphalt concrete.
[0042] like Figure 3 As shown, a copper plate electrode 5 with a thickness of 1 mm was placed on both sides of the crack damage 6 of the asphalt concrete bending beam that reached the fatigue end condition, and a DC power supply with a constant power of 50 W was used to perform electrothermal self-healing curing for 24 hours, and then the asphalt concrete bending beam was left to stand for 24 hours at 20°C, and the above fatigue test was performed on the asphalt concrete bending beam again. The fatigue life recovery rate was used to evaluate the self-healing effect of asphalt concrete, that is, the increased fatigue life after healing / fatigue life.
[0043] The results show that the fatigue life recovery rate of the graphene aerogel self-repairing asphalt concrete bending beam after electrothermal self-repairing maintenance reaches 88.3%.
[0044] Embodiment 3:
[0045] A graphene aerogel self-repairing asphalt concrete of this embodiment 3 is composed of an asphalt mixture matrix 1 and a graphene aerogel-shaped asphalt self-repairing agent 2 distributed in the asphalt mixture matrix 1. The addition amount of the graphene aerogel-shaped asphalt self-repairing agent 2 is 0.2% of the total mass of the graphene aerogel self-repairing asphalt concrete. During the mixing process of the asphalt mixture matrix 1, the graphene aerogel-shaped asphalt self-repairing agent 2 is added to obtain the graphene aerogel self-repairing asphalt concrete.
[0046] The graphene aerogel-shaped asphalt self-repairing agent 2 is composed of a graphene aerogel matrix 3 and an asphalt regeneration agent 4 filled in the pores of the graphene aerogel matrix 3. The graphene aerogel matrix 3 is a granular graphene aerogel matrix prepared by a hydrothermal reduction method, with an average particle size of 10 μm and a porosity of 30%. The asphalt regeneration agent 4 is loaded into the graphene aerogel matrix 3 by a vacuum adsorption method, thereby obtaining the graphene aerogel-shaped asphalt self-repairing agent 2.
[0047] Asphalt concrete slabs of 400mm×300mm×75mm were made according to the vibration wheel rolling method and cut into curved beams. The American AASHTO T321 standard was used to carry out strain-controlled four-point bending fatigue test and determine the fatigue life of the asphalt concrete.
[0048] For example, a copper plate electrode 5 with a thickness of 1 mm is placed on both sides of the crack damage 6 of the asphalt concrete bending beam that has reached the fatigue end condition, and a DC power supply with a constant electric power of 10 W is used to perform electrothermal self-healing maintenance for 24 hours, and then it is left to stand at 20°C for 24 hours, and the above-mentioned fatigue test is performed on the asphalt concrete bending beam again.
[0049] Embodiment 4:
[0050] A graphene aerogel self-repairing asphalt concrete of this embodiment 4 is composed of an asphalt mixture matrix 1 and a graphene aerogel-shaped asphalt self-repairing agent 2 distributed in the asphalt mixture matrix 1. The addition amount of the graphene aerogel-shaped asphalt self-repairing agent 2 is 3.0% of the total mass of the graphene aerogel self-repairing asphalt concrete. During the mixing process of the asphalt mixture matrix 1, the graphene aerogel-shaped asphalt self-repairing agent 2 is added to obtain the graphene aerogel self-repairing asphalt concrete.
[0051] The graphene aerogel-shaped asphalt self-repairing agent 2 is composed of a graphene aerogel matrix 3 and an asphalt regeneration agent 4 filled in the pores of the graphene aerogel matrix 3. The graphene aerogel matrix 3 is a granular graphene aerogel matrix prepared by a hydrothermal reduction method, with an average particle size of 20 mm and a porosity of 99%. The asphalt regeneration agent 4 is loaded into the graphene aerogel matrix 3 by a vacuum adsorption method, thereby obtaining the graphene aerogel-shaped asphalt self-repairing agent 2.
[0052] Asphalt concrete slabs of 400mm×300mm×75mm were made according to the vibration wheel rolling method and cut into curved beams. The American AASHTO T321 standard was used to carry out strain-controlled four-point bending fatigue test and determine the fatigue life of the asphalt concrete.
[0053] For example, a copper plate electrode 5 with a thickness of 1 mm is placed on both sides of the crack damage 6 of the asphalt concrete bending beam that has reached the fatigue end condition, and a DC power supply with a constant electric power of 200 W is used to perform electrothermal self-healing maintenance for 24 hours, and then it is left to stand at 20°C for 24 hours, and the above-mentioned fatigue test is performed on the asphalt concrete bending beam again.
[0054] Embodiment 5:
[0055] Compared with Example 1, most of them are the same, except that the graphene aerogel matrix 3 is a fiber-type graphene aerogel matrix prepared by a hydrothermal reduction method, with a length of 20 mm, a diameter of 10 μm, and a porosity of 50.3%.
[0056] Embodiment 6:
[0057] Compared with Example 1, most of them are the same, except that the graphene aerogel matrix 3 is a fiber-type graphene aerogel matrix prepared by a hydrothermal reduction method, with a length of 20 mm, a diameter of 500 μm, and a porosity of 78.6%.
[0058] Comparative Example 1:
[0059] Compared with Example 1, most of them are the same, except that the asphalt concrete matrix does not contain graphene aerogel-shaped asphalt self-healing agent.
[0060] The fatigue test results show that the fatigue life recovery rate of the asphalt concrete bending beam without the graphene aerogel-shaped asphalt self-repairing agent is only 14.7%. The fatigue life recovery rate of the graphene aerogel self-repairing asphalt concrete bending beam in Example 1 reaches 76.9%. This shows that the graphene aerogel self-repairing asphalt concrete containing the graphene aerogel-shaped asphalt self-repairing agent has a relatively ideal self-repairing effect.
[0061] Comparative Example 2:
[0062] Compared with Example 1, most of them are the same, except that there is no asphalt regeneration agent 4 filled in the graphene aerogel matrix 3.
[0063] After fatigue testing, the results show that the fatigue life recovery rate of the graphene aerogel self-repairing asphalt concrete curved beam without asphalt regeneration agent 4 is 19.0%, while the fatigue life recovery rate of the graphene aerogel self-repairing asphalt concrete curved beam filled with asphalt regeneration agent 4 in Example 1 reaches 76.9%. The fatigue life recovery rate of the asphalt concrete curved beam without graphene aerogel shaped asphalt self-repairing agent in Comparative Example 1 is only 14.7%, indicating that the addition of graphene aerogel matrix 3 can effectively improve the fatigue resistance of asphalt concrete.
[0064] Comparative Example 3:
[0065] Compared with Example 2, most of the aspects are the same, except that the electric heat-induced self-healing curing is not used, and the fatigue test is performed on the asphalt concrete bending beam after standing at 20°C for 48 hours.
[0066] The results show that the fatigue life recovery rate of the graphene aerogel self-repairing asphalt concrete curved beam without electrothermal self-healing maintenance is 76.9%, while the fatigue life recovery rate of the graphene aerogel self-repairing asphalt concrete curved beam after electrothermal self-healing maintenance in Example 2 reaches 88.3%, indicating that the graphene aerogel self-repairing asphalt concrete containing graphene aerogel shaping asphalt self-healing agent has relatively ideal self-repairing performance, and the electrothermal self-healing maintenance incentive mechanism can further effectively enhance the self-repair effect of the asphalt concrete matrix.
[0067] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. An application of graphene aerogel self-repairing asphalt concrete, characterized in that: The graphene aerogel self-repairing asphalt concrete is composed of an asphalt mixture matrix and a graphene aerogel-shaped asphalt self-repairing agent distributed in the asphalt mixture matrix; The graphene aerogel-shaped asphalt self-repairing agent is composed of a graphene aerogel matrix and an asphalt regeneration agent filled in the pores of the graphene aerogel matrix. The addition amount of the graphene aerogel-shaped asphalt self-repairing agent is 0.2-3.0% of the total mass of the graphene aerogel self-repairing asphalt concrete. The graphene aerogel self-repairing asphalt concrete is applied in the field of electrothermal self-repairing.
2. The application of graphene aerogel self-repairing asphalt concrete according to claim 1, characterized in that: The graphene aerogel matrix is a three-dimensional porous aerogel composed of carbon nanomaterials.
3. The application of graphene aerogel self-repairing asphalt concrete according to claim 2, characterized in that: The carbon nanomaterial is selected from one or more of graphene and carbon nanotubes.
4. The application of graphene aerogel self-repairing asphalt concrete according to claim 1, characterized in that: The porosity of the graphene aerogel matrix is 30%-99%.
5. The application of graphene aerogel self-repairing asphalt concrete according to claim 1, characterized in that: The graphene aerogel matrix is selected from one or more of a fiber-type graphene aerogel matrix, a particle-type graphene aerogel matrix, and a fiber-type graphene / carbon nanotube composite aerogel matrix.
6. The use of graphene aerogel self-repairing asphalt concrete according to claim 5, characterized in that: The fiber-type graphene aerogel matrix has a length of 6-20 mm and a diameter of 10-500 μm; the particle size of the particle-type graphene aerogel matrix is 10-20 mm; the fiber-type graphene / carbon nanotube composite aerogel matrix has a length of 6-20 mm and a diameter of 10-500 μm.
7. The application of graphene aerogel self-repairing asphalt concrete according to claim 1, characterized in that: In the application of electrothermal self-repairing, the graphene aerogel self-repairing asphalt concrete is stimulated by a constant electric power of 10-200 W.
Citation Information
Patent Citations
Self-healing asphalt concrete based on fiber type self-repairing agent
CN112939513A
Three-dimensional integral graphene aerogel-polyimine composite material and preparation method thereof
CN113121953A